2019
DOI: 10.1007/s42729-019-00106-y
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Improve Soil Quality: a Case Study of Straw Incorporation with a Decomposer Under Full Film-Mulched Ridge-Furrow Tillage on the Semiarid Loess Plateau, China

Abstract: There is limited understanding of the effects of straw incorporation with decomposition agent (refer to decomposer) under full plastic film-mulched ridge-furrow tillage (FM) on straw decomposition rate and soil fertility. A direct field incubation test of straw with and without decomposer (T1 and T2) under FM using the litter bag method and a 3-year field experiment of five treatments including conventional planting (CP, as control), CP with straw incorporation (CP S), CP with straw incorporation plus decompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…In our experiment, with increasing temperature and rainfall for the 0-95d after straw return to the field, overall decomposition proportion, carbon release proportion and cellulose, hemicellulose, and lignin decomposition proportion of all treatments were similar, that is, they increased rapidly (Fig. 1), our finding was consistent with the work of Yang et al 35 . During the 95d-145d period, a drop in temperature and precipitation occurs, microbial decomposition activity slows down, due to the perishable nature of straw, components such as cellulose and hemicellulose gradually decline, refractory organic components such as lignin proportion increase, so straw decomposition gradually slows, and late decomposition proportion is significantly reduced 36 .…”
Section: Discussionsupporting
confidence: 92%
“…In our experiment, with increasing temperature and rainfall for the 0-95d after straw return to the field, overall decomposition proportion, carbon release proportion and cellulose, hemicellulose, and lignin decomposition proportion of all treatments were similar, that is, they increased rapidly (Fig. 1), our finding was consistent with the work of Yang et al 35 . During the 95d-145d period, a drop in temperature and precipitation occurs, microbial decomposition activity slows down, due to the perishable nature of straw, components such as cellulose and hemicellulose gradually decline, refractory organic components such as lignin proportion increase, so straw decomposition gradually slows, and late decomposition proportion is significantly reduced 36 .…”
Section: Discussionsupporting
confidence: 92%
“…In our experiment, with the straw incorporation and tillage practices, the soil structure was reorganized, resulting in the decrease in the soil bulk density and increase in the soil porosity. Yang et al [46] revealed that straw incorporation after three years decreased the soil bulk density in the 0-30 cm soil layer by 1.6%-4.7%, which was consistent with our results. Choudhary et al [47] also reported that soil application with crop residues could mitigate the adverse effect of saline water irrigation.…”
Section: Main Effects Of Straw Segment Length On Soil Propertiessupporting
confidence: 93%
“…Previously, Wang et al (2015b) found that straw incorporation could improve NUE due to the improvement of N immobilization. In addition, Yang et al (2020) reported that complete decomposition of straw leads to the enhancement release of straw C and N into the soil which improved soil nutritional condition. However, Hoang and Marschner (2019) found that straw addition could decrease available N, compared with without straw addition.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%